Preparing Graduates for Interprofessional Practice in South Africa: The Dissonance Between Learning and Practice - Müller, Jana; Couper, Ian (Frontiers in Public Health, 2021)
With South Africa’s tumultuous history and resulting burden of disease and disability persisting post-democracy in 1994, a proposed decentralisation of heath care with an urgent focus on disease prevention strategies ensued in 2010. Subsequently a nationwide call by students to adapt teaching and learning to an African context spoke to the need for responsive health professions training. Institutions of higher education are therefore encouraged to commit to person-centred comprehensive primary health care (PHC) education which equates to distributed training along the continuum of care. To cope with the complexity of patient care and health care systems, interprofessional education and collaborative practice has been recommended in undergraduate clinical training. Stellenbosch University, South Africa, introduced interprofessional home visits as part of the students’ contextual PHC exposure in a rural community in 2012. This interprofessional approach to patient assessment and management in an under-resourced setting challenges students to collaboratively find local solutions to the complex problems identified. This paper reports on an explorative pilot study investigating students’ and graduates’ perceived value of their interprofessional home visit exposure in preparing them for working in South Africa. Qualitative semi-structured individual and focus group interviews with students and graduates from five different health sciences programmes were conducted. Primary and secondary data sources were analysed using an inductive approach. Thematic analysis was conducted independently by two researchers and revealed insights into effective patient management requiring an interprofessional team approach. Understanding social determinants of health, other professions’ roles, as well as scope and limitations of practice in a resource constrained environment can act as a precursor for collaborative patient care. The continuity of an interprofessional approach to patient care after graduation was perceived to be largely dependent on relationships and professional hierarchy in the workplace. Issues of hierarchy, which are often systemic, affect a sense of professional value, efficacy in patient management and job satisfaction. Limitations to using secondary data for analysis are discussed, noting the need for a larger more comprehensive study. Recommendations for rural training pathways include interprofessional teamwork and health care worker advocacy to facilitate collaborative care in practice.